Understanding the Impact of e-Filing System Performance on Tax Compliance Using the DeLone and McLean Model - Nyoman Yudha Astriayu Widyari; Dodik Ariyanto; Herkulanus Bambang Suprasto; I Dewa Gede Dharma Suputra (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
This study aims to investigate the impact of e-filing system performance on tax compliance applying DeLone and McLean IS Success Model. The study samples are 128 Indonesian micro, small, and medium entrepreneur (MSME) that selected using proportional random sampling. Data was collected using questionnaires and analyzed using SEM-PLS. The results showed that information quality and service quality have a positive effect on system use. In addition, information quality and system quality positively affect user satisfaction. By contrast, there is no impact of trust in e-government to either system use and user satisfaction. System use and user satisfaction positively influence taxpayers’ compliance. Meanwhile, gender does not moderate the effect of system use and user satisfaction on tax compliance.